Children's lived experiences of 'ability' in the Key Stage One classroom: life on the 'tricky table'. Issue 5 (2nd September 2020) - Gripton, Catherine
ABSTRACT: Within the wealth of research on 'ability' in education, there is a missing perspective: the perspective of the child. Whilst 'ability' informed practices such as 'ability' grouping are commonplace in the UK, how these are experienced by the young child has previously received only limited attention in research. Using case study evidence, this article demonstrates that children's lived experiences of 'ability' are highly individual and shaped by a broader range of social, structural and pedagogic aspects of classroom life than previously thought. Implications are that a wide range of teaching choices can potentially affect a child's experience of 'ability' and that the impact of these are particularly profound for some children, shaping their perceptions of themselves and others. Children's perspectives therefore offer a challenge to the hegemonic discourse of 'ability' in education and the classroom practices upon which it is based.